Geometrical Space Diversity And Distributed Space Diversity Techniques For Wireless Communication Systems - Faedfar, Yaser (2013)
This research produces a novel space diversity scheme based on geometrical concept for optimizing the Signal to Noise Ratio (SNR) of the equal-gain Multiple Input and Single Output (MISO) communication system. In the second stage, this method is extended to Multiple Input and Multiple Output (MIMO) systems. These methods are proposed to solve the main problems of the conventional closed-loop MISO and MIMO systems such as high Complexity, feedback delay, the unknown average SNRs, dependant on transmit antennas, non-adaptivity to channels, and phase ambiguity. In the third stage, the structure of the proposed Scalar Equal Gain Transmission and Generalized Maximum Ratio Combining (SEGT/GMRC) scheme is followed to design the limited-feedback codebooks for MISO and MIMO systems which provide a different methodology as compared to the previous well-known codebooks. The proposed quantized equal-gain (QE) codebooks, requires the minimum number of feedback bits to form the beamforming vector. In the fourth stage, the proposed QE codebooks are employed to provide the distributed spatial diversity in a wireless relay network. Since transmit antennas are independent, the extension to relay network is straightforward. The new design is named Distributed QE (DQE) codebooks, in which each relay node stores a QE codebook. In this research, the wireless open-access research platform (WARP) is employed for prototyping the proposed QE codebooks. The proposed new geometrical space diversity system eliminates the searching process and serves as the optimal system for equal-gain MISO transmission systems.